Optimalisasi Proses Perpajakan Melalui Sistem Terintegrasi pada Perusahaan Jasa Kepelabuhanan - Marshall Sava Laksa Muhammad Wibisono; Ade Irma Suryani Lating (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
The digital era requires companies to adapt to modern, efficient, and accurate taxation systems. This study aims to analyze the implementation of an integrated system to optimize tax administration processes in a port service company in Indonesia. The focus of this research is to examine how the integration of systems such as SAP, Coretax, Microsoft Excel, and digital banking platforms is utilized to manage Income Tax Article 23 (PPh 23), Value Added Tax (VAT), and the tax reimbursement process. This study employs a qualitative approach with a descriptive case study design, conducted through participatory observation, document analysis, and informal interviews with employees directly involved in tax administration. The results indicate that the integrated system positively impacts the efficiency, consistency, and reliability of tax administration processes. It helps streamline workflows and accelerate tax reporting, particularly in managing PPh 23 and VAT. However, weaknesses remain in the manual data recap stage using Microsoft Excel, which is prone to human error due to the absence of automatic validation mechanisms. Therefore, this study recommends developing a standardized Excel template equipped with automatic validation features and providing training for staff to enhance data accuracy and administrative effectiveness. These findings are expected to serve as a practical reference for other companies in implementing an integrated taxation system that is optimal and sustainable, as well as encouraging increased efficiency and compliance with tax administration in the corporate environment.